A Case Report: Coccidiosis in Layer Farm, Sumedang - Hartady, Tyagita; Darmesti, Daniswara Danindra; Hermawan, Firda Aisyah; Khairani, Shafia; Windria, Sarasati; Wismandanu, Okta; Rosdianto, Aziiz Mardanarian; Satryo, Faisal Amri (Media Kedokteran Hewan, 2024)
Coccidiosis is a parasitic disease that causes economic losses on chicken farms. A case was found on a farm in Rancaekek, Bandung Regency, where there was a one-year-old laying hen that stopped producing eggs, experienced decreased pectoral muscle mass, and had mild ataxia. The diagnosis was made by necropsy procedure and fecal examination. There were lesions in the small intestine, these lesions manifested as ballooning filled with orange mucus and the presence of petechial hemorrhages on the luminal wall and decreased pectoral muscle mass was found. A Fecal examination was performed using the floating method and the McMaster calculation. The results of the fecal examination revealed Eimeria sp. oocysts and Trichostongylus tenuis eggs. The diagnosis of this case is coccidiosis infection caused by two species of Eimeria sp., namely Eimeria maxima and Eimeria tenella. This infection has resulted in a nutritional deficiency, manifested by a decrease in pectoral muscle mass.